The Importance of Teaching Primary Students Mother Tongue Multiple Meaning Words - Sodiqova Gulbahor G’ofurjon qizi (Global Scientific Publishing, 2023)
In this article, when explaining the meaning of a polysemous word to elementary school students, it is necessary to reveal its semantic structure and the connection between the main meaning and the figurative meaning. Ideas are given about the connection between the meanings of polysemous words. There are specific practical aspects of working on ambiguous words, and the article is enriched with examples based on textbooks to pay special attention to this practical importance
Keywords: Multiple meaning words; semantic structure of words